2001
DOI: 10.1071/pp00143
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between reactive oxygen species and nitric oxide in drought-induced abscisic acid synthesis in root tips of wheat seedlings

Abstract: Abscisic acid accumulation and oxidative stress are two common responses of plants to environmental stresses. However, little is known about their relationships. The purpose of this article is to investigate the effects of reactive oxygen species and nitric oxide on the plant hormone abscisic acid synthesis in root tips of wheat (Triticum aestivum L.) seedlings under drought stress. Detached root tips were subjected to drought stress by naturally evaporating until 20% of their fresh weights were lost. The acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 36 publications
2
66
0
4
Order By: Relevance
“…Whether a model such as that described above exists in plants exposed to water stress is an interesting topic. Although it has been shown that dehydration results in significant increases in the activity of superoxide synthase [NAD(P)H oxidase] in the microsomal and cytosolic fractions from rapidly, severely dehydrated root tips of wheat seedlings (20% of fresh weight lost in about 10 min; Zhao et al 2001), it is not clear whether these changes are physiologically related. Furthermore, these experiments also did not exclude the possible involvement of the NAD(P)H-oxidizing activity of peroxidase.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Whether a model such as that described above exists in plants exposed to water stress is an interesting topic. Although it has been shown that dehydration results in significant increases in the activity of superoxide synthase [NAD(P)H oxidase] in the microsomal and cytosolic fractions from rapidly, severely dehydrated root tips of wheat seedlings (20% of fresh weight lost in about 10 min; Zhao et al 2001), it is not clear whether these changes are physiologically related. Furthermore, these experiments also did not exclude the possible involvement of the NAD(P)H-oxidizing activity of peroxidase.…”
Section: Discussionmentioning
confidence: 98%
“…These observations have demonstrated the existence of a plant NADPH oxidase resembling the neutrophil NADPH oxidase. It has been shown that NADPH oxidase is involved in plant growth and development (Papadakis and Roubelakis-Angelakis 1999;Frahry and Schopfer 2001;Schopfer et al 2001), and in plant response to pathogens, elicitors and wounding (Lamb and Dixon 1997;Bolwell et al 1998;Orozco-Ca´rdenas and Ryan 1999;Orozco-Ca´rdenas et al 2001;Sagi and Fluhr 2001), UV light (Rao et al 1996;A.-H.-Mackerness et al 2001), hypoosmotic stress (Cazale´et al 1998Park et al 2000), zinc and copper deficiency or excess (Pinton et al 1994;Quartacci et al 2001), chilling (Shen et al 2000) and drought (Zhao et al 2001), and plays important roles in AOS production and the regulation of defense strategies in plant cells (Levine et al 1994;Lamb and Dixon 1997;A.-H.-Mackerness et al 2001;Orozco-Ca´rdenas et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, H 2 O 2 activates plasma membrane Ca 2ϩ channels and induces stomatal closure in abi1 but not in abi2 (25). Recently, it was suggested that reactive oxygen species might also be involved in the regulation of ABA biosynthesis (26). It is likely that the observed ABA regulation of ABA biosynthesis genes may be mediated by reactive oxygen species.…”
Section: Los6 Encodes An Enzyme Functioning In Aba Biosynthesis-mentioning
confidence: 94%
“…The NO releasing chemical (SNP), NOS inhibitor (LNNA), NO scavenger (PTIO), and ROS eliminator (NAC) (Zhao et al 2001;Wang et al 2006), were purchased from Sigma, NY, USA, and were applied in vivo by injection (Chen et al 1993) into the intercellular space of maize seedlings through the roots incubated in 300 mL Hoagland's solution containing 0.1 mM SNP or 0.2 mM LNNA or 0.2 mM PTIO or 0.05 mM NAC (regenerated once a day and the hydroponics were aerated as much as three times for 20-30 min/time with air pump) with or without the UV-B treatments. Hoagland's solution was used as a control treatment.…”
Section: Ultraviolet-b Treatmentmentioning
confidence: 99%